Thyroid function in dogs with visceral leishmaniasis - Cardoso, Mauro José Lahm; Melussi, Maira; Fagnani, Rafael; Holsback, Luciane; Patelli, Thais Helena Constantino; Oba, Eunice [UNESP] (My University, 2014)
Several non-thyroid factors such as age, breed, concomitant diseases and use of certain drugs might influence the diagnosis of hypothyroidism in dogs. Changes in the concentrations of thyroid hormones due to non-thyroid illnesses are named euthyroid sick syndrome. Among the diseases with potential to provoke a decrease in thyroid hormones there are infecto-contagious diseases such as parvovirosis, babesiosis and leishmaniasis. Canine visceral leishmaniasis is a severe systemic disease which may cause kidney and liver diseases, cardiac injuries and injuries to other organs. The aim of this study was to evaluate the influence of visceral leishmaniasis on thyroid function in dogs without signs of hypothyroidism with or without azotemia. Positive animals for leishmaniasis were divided in six groups regarding: absence of hypoalbuminemia, presence of hypoalbuminemia, normal creatinine, increased creatinine, normal urea and increased urea. The effect of these groups was evaluated on the thyroid-stimulating hormone, total thyroxine and free thyroxine concentrations. Dogs that were positive for leishmaniasis (0.63 ng mL-1) presented thyroid-stimulating hormone serum concentrations higher than seronegative animals (0.43 ng mL-1) while total thyroxine (1.28 μg dL-1) and free thyroxine (1.49 ng dL-1) in dogs with leishmanisis were lower (p<0.01) when compared to healthy dogs (total thyroxine for 2.31 μg dL-1 and free thyroxine 1.84 ng dL-1) however, within the values for euthyroid animals. In dogs seropositive for leishmaniasis, total thyroxine means in the group with the presence of hypoalbuminemia (1.01 μg dL-1) were lower (p<0.04) when compared to the means in the group with absence of hypoalbuminemia (1.4 μg dL-1). Based on this study, it can be concluded that dogs that were positive to visceralleishmaniasis did not develop euthyroid sick syndrome, although compared to normal thyroid hormones were reduced.
Keywords: Euthyroid; Sick syndrome; Leishmania; Hypthyroidism; Thyroxine; Hypoalbuminemia